Respostas
respondido por:
0
A
B C
Traçando de "A" uma ⊥ à BC até encontrar em "D"
Δ ADB ⇒ retângulo isósceles
seja "y" =BD = AD
y² + y² = (3√2)²
2y² = 18
y² = 9
y = 3
Δ ADC ⇒ retângulo
_AD_ = sen 60°
x
como AD = y
_y_= sen 60°
x
_3_ = _√3_
x 2
x = _6_ ⇒ x = _6√3_ ⇒ x = 2√3cm
√3 √3√3
B C
Traçando de "A" uma ⊥ à BC até encontrar em "D"
Δ ADB ⇒ retângulo isósceles
seja "y" =BD = AD
y² + y² = (3√2)²
2y² = 18
y² = 9
y = 3
Δ ADC ⇒ retângulo
_AD_ = sen 60°
x
como AD = y
_y_= sen 60°
x
_3_ = _√3_
x 2
x = _6_ ⇒ x = _6√3_ ⇒ x = 2√3cm
√3 √3√3
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás